FREQUENCY ANALYSIS OF DELI RIVER FLOOD DISTRIBUTION PLAN USING THE GUMBEL PROBABILITY DISTRIBUTION METHOD - Agustin, Uni; Siregar, Machrani Adi Putri (Sinkron : jurnal dan penelitian teknik informatika, 2023)
The Deli river basin is one of the rivers in North Sumatra Province which is in Medan City with an area of ​​394.88 km2 and a length of 166.01 km. Medan Maimun District which has an area of ​​2.98 km2 and a population density of 16,520 people/km2. Medan Mimun sub-district is one of the flood-prone areas which is drained by the Deli River. The cause of the flooding that occurred in Medan Maimun District was high rainfall so that the river flow rate increased and drainage was poor. So that the problem of flooding in the Deli river watershed, Medan Maimun sub-district, can hamper community activities, these floods can also harm and endanger the community. The flood discharge plan for each repeat period where the variable used is the maximum daily rainfall for 10 years From 2013-2022 which is sourced from the BMKG Deli Serdang. In this study using frequency analysis and then proceed with the Gumbel Probability Distribution method, Normal Distribution Log Person Type III. The result of this study with hydrological data and distribution test, the suitable method for analyzing the planned flood discharge in the Deli River is Log Person Type III that it can be flood discharge for a 2 year retention period is 12.7684672 m3/sec, 5 year return period is 12.56275855 m3/sec, 10 year return period is 15.91400029 m3/sec, 25 year return period is 16.87871678 m3/sec, 50 year return period is 17.43836748 m3/sec and a 100 year return period is 17.89619614 m3/sec. Keywords: Rainfall, Deli River, Planned Flood Discharge